Goldilocks zone of lignin: Two extremes of valve lignification lead to silique indehiscence in Brassicaceae - Justin B. Nichol; Logan A. Skori; Muhammad Jamshed; Neil Hickerson; Mendel Perkins; Marcus A. Samuel (Proceedings of the National Academy of Sciences, 2025)
The spring-loaded spontaneous seed dispersal mechanism known as dehiscence, has been a critical plant feature for the successful colonization of land by angiosperms. Although advantageous for seed dispersal, spontaneous dehiscence is largely an unfavorable agronomic trait which historically was selected against during selective breeding of crops to increase seed retention. In canola ( Brassica napus ), a major global oil seed crop, spontaneous or harsh weather-induced fruit shattering at maturity could lead to yield losses from 3 to 50%. Here, we show an extraembryonic role for the ABA-responsive transcription factor, ABSCISIC ACID INSENSITIVE-3 (ABI3) in controlling seed dispersal through mediating lignification of the endocarp b (en b ) layer and the lignified layer (LL) of the valves. The resistance created by these lignified layers is critical for valve opening at maturity as the tensile forces generated during silique drying converge on these fortified cell layers to trigger shatter. We further show that ABI3 functions independent of the patterning genes and functions through transcriptional regulation of NAC-domain transcription factors, NST1 and NST3 , to mediate lignin biosynthesis. Our results show that both excessive and complete absence of lignification could prevent the tensile drying forces from breaking open the pod, leading to fruit indehiscence. As a proof-of-concept, we show that BnABI3 overexpression in canola results in highly lignified, robust siliques that are shatter tolerant. Besides uncovering an extraembryonic role for ABI3, this study has identified spatial distribution and abundance of lignin in the silique valve tissue as the key determinants for silique dehiscence.